2007
DOI: 10.1088/0960-1317/18/1/015023
|View full text |Cite
|
Sign up to set email alerts
|

A piezoelectric microvalve for cryogenic applications

Abstract: This paper reports on a normally open piezoelectrically actuated microvalve for high flow modulation at cryogenic temperatures. One application envisioned is to control the flow of a cryogen for distributed cooling with a high degree of temperature stability and a small thermal gradient. The valve consists of a micromachined die fabricated from a silicon-on-insulator wafer, a glass wafer, a commercially available piezoelectric stack actuator and Macor TM ceramic encapsulation that has overall dimensions of 1 ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…The fabrication process is a variant of the process previously used to create flexure suspended microvalves [20]. Steps have been added to the process to create the embedded sensors, and other steps have been altered to increase yield and decrease process complexity.…”
Section: Device Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…The fabrication process is a variant of the process previously used to create flexure suspended microvalves [20]. Steps have been added to the process to create the embedded sensors, and other steps have been altered to increase yield and decrease process complexity.…”
Section: Device Fabricationmentioning
confidence: 99%
“…For this paper, piezoelectric actuation is used, to allow proportional flow control, to generate high force, and to minimize the power consumption. Piezoelectric microvalves without integrated sensors have been developed for space applications [18], [19] and in our previous work, they have been shown to work in a cryogenic environment [20].…”
mentioning
confidence: 99%
“…The SMA-wire-actuated microvalve also offers the lowest power consumption with respect to existing high-flow microvalves, and is only outperformed by PZT microvalves, which however provide an order of magnitude lower flow rate per footprint. The SMA wire actuator valve has more than one order of magnitude lower power consumption than the gate valves with in-plane actuation [9,10] and has two [4] 6 .3 × 6.6 0% 0.8 W n/a n/a Park et al (seat valve, PZT) [5] 1 orders of magnitude lower voltage than the PZT microvalve [5]. The main drawback of the SMA wire valve compared to the other valves is the high relative leakage.…”
Section: Comparison To Previous Workmentioning
confidence: 99%
“…Only basic calculations have been performed to assess its performance-the in depth analysis and refinement of this design will be the subject of future work. The use of cryogenic propellants has not been taken into account since few data exist relative to the capability of PZT to work at cryogenic temperatures even though work by Park et al [24] has demonstrated a PZT actuated microvalve that operates down to 40 K.…”
Section: Active Injection-a Design Ideamentioning
confidence: 99%